The Role of the Father in Anne Tyler’s Saint Maybe: An Overview - Alias, Merna Thaer; Taher, Isra Hashim (Al-Adab Journal, 2021)
The role of the father has always been that of the breadwinner of the family in most of the American novels. Little was mentioned about his involvement in his familial duties and his relationship with his children. This created a gap between the father and his children and turned him into a far-fetched person for them. Anne Tyler (1941- ), a southern female writer presents a new image of fathers. She highlights the role of the father within the family and gives an insight to the way fathers think. This paper deals with Tyler’s novel Saint Maybe (1991), exploring the character of Ian Bedloe, an unmarried person whose mistake leads him to lose his only brother, Danny. He suffers for his mistake and tries to make up for it by taking care of his brother’s children offering a new image of fatherhood.